Acquisition of coronal alignment according to the degree of varus deformity in total knee arthroplasty using computer-assisted navigation. (28th May 2020) - Song, Suk Kyoon; Cho, Myung Rae; Lee, Seo Ho; Kim, Hee Chan; Kang, Dae won; Choi, Won-Kee
Purpose: We have analyzed the surgical outcomes of primary total knee arthroplasty (TKA) using computer-assisted navigation that were performed by a single surgeon in terms of postoperative coronal alignment depending on preoperative varus deformity. Methods: We conducted a retrospective study of patients who have undergone navigated primary TKA from January 2016 through December 2019. Two hundred and fifty-six cases with varus deformity of 10° or less were assigned to group 1, and 216 cases with varus deformity of more than 10° were assigned to group 2. The postoperative mechanical hip–knee–ankle (mHKA) angle was measured from scanograms which were taken preoperatively and 3 months after surgery. The postoperative mHKA angle was targeted to be 0°, and the appropriate range of coronal alignment was set as 0 ± 3°. Results: The Pearson correlation showed a significant correlation with the degree of preoperative varus deformity and with the absolute error of postoperative mHKA ( p = 0.01). Among all patients, 64 cases (13.6%) were detected as outliers (mHKA > 0° ± 3°) at 3 months after surgery. Of the 64 cases, 25 cases (9.8%) were affiliated to group 1 and 39 cases (18.1%) were affiliated to group 2. Group 2 showed significantly higher occurrence of outliers than group 1 ( p = 0.01). Multiple variables logistic regression analysis, which analyzed the difference in the occurrence rate of outliers (mHKA > 0° ± 3°), showed that the occurrence rate of group 2 was 2.04 times higher than group 1. After adjusting for patient's age, gender, and body mass index, the occurrence rate of outliers in group 2 was 2.01 times higher than group 1. Conclusion: The benefit of computer-assisted navigation during TKA in obtaining coronal alignment within 0 ± 3° may be lessened when the preoperative varus deformity is severely advanced.